2004
DOI: 10.1111/j.0141-9838.2004.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

CTLA‐4 regulates the murine immune response to Trypanosoma cruzi infection

Abstract: Infection with Trypanosoma cruzi causes a profound suppression of T cell responsiveness to polyclonal or antigenic stimuli. In this study, we quantified expression of the negative T cell regulatory molecule CTLA-4 in T. cruzi infected mice and analysed its influence on the immune suppression. Levels of splenic CTLA-4 expression were highest around day 10 after infection, reaching 5% in resistant B6D2F1 mice, but exceeding 10% of CD4(+) T cells in C57BL/6 mice that were susceptible to mortal disease. The prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…It was also demonstrated that CTLA-4 blockade ameliorated the outcome of the disease and increased survival rate [52]. Likewise, the expression of another inhibitory receptor, the Programmed death cell receptor 1 (PD-1), has been shown to be increased by spleen-derived T lymphocytes [53], as well as in lymphocytes infiltrating heart tissues in response to acute T. cruzi infection in mice, while PD-1 blockade led to reduced tissue parasitemia but increased mortality [53].…”
Section: Discussionmentioning
confidence: 94%
“…It was also demonstrated that CTLA-4 blockade ameliorated the outcome of the disease and increased survival rate [52]. Likewise, the expression of another inhibitory receptor, the Programmed death cell receptor 1 (PD-1), has been shown to be increased by spleen-derived T lymphocytes [53], as well as in lymphocytes infiltrating heart tissues in response to acute T. cruzi infection in mice, while PD-1 blockade led to reduced tissue parasitemia but increased mortality [53].…”
Section: Discussionmentioning
confidence: 94%
“…CTLA-4 is mainly co-expressed on CD4 + CD25 + Foxp3 + T cells (Akbari et al, 2003), and these cells play a crucial role not only in autoimmune diseases and transplant rejection but also in persistent infection and the pathogenesis of chronic viral infection. The presence of CTLA-4 on CD4 + CD25 + Foxp3 + T cells has been regarded as an explanation for immunosuppression during disease progression in infections with HIV, SIV, HCV, and Trypanosoma and in B cell non-Hodgkin lymphoma (Boasso et al, 2007;Graefe et al, 2004;Kaufmann and Walker, 2009;Leng et al, 2002;Nakamoto et al, 2009;Yang et al, 2006;Zaunders et al, 2006;Zhang et al, 2010). In the model of HTLV-I-related BLV, Foxp3-and CTLA-4-expressing HTLV-I-infected cells suppressed the proliferation of naïve T cells that were stimulated with anti-CD3 antibody (Takayanagi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…CTLA-4 was preferentially upregulated in programmed death-1 (PD-1)-expressing CD8 + T cells from the liver but not blood of chronically HCV-infected patients, and PD-1/CTLA-4 coexpression in intrahepatic T cells was associated with profound HCV-specific effector dysfunction (Nakamoto et al, 2009). CTLA-4 also showed correlations with T cell dysfunction and disease severity in Chagas disease caused by the protozoan parasite Trypanosoma cruzi (de Araújo et al, 2012;Graefe et al, 2004). Furthermore, CTLA-4 was elevated during tumor development, resulting in increased levels of CD4 + CD25 + Foxp3 + Tregs at tumor sites and subsequent induction of tumor tolerance systems (Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of a blocking CTLA-4-specific antibody resulted in increased resistance to infection with the Y and Colombian strains of T. cruzi [46]. In another study, CTLA-4 blockade at the time of infection with the Tulahuen strain of T. cruzi also ameliorated the course of the disease and led to an increased survival rate [47]. In human Chagas disease, exposure of lymphocytes to T. cruzi infected monocytes increased the expression of CTLA-4 on T cells from indeterminate but not cardiac patients [48].…”
Section: Ctla-4/b7 Interactions In Parasitic Infec-tionsmentioning
confidence: 95%
“…enhanced efficacy of a vaccination against P. berghei liver-stage malaria upon CTLA-4 blockade [67] increased resistance of mice to infection with the Y and Colombian strains of T. cruzi upon CTLA-4 blockade [46] increased survival rate during infection of mice with the Tulahuen strain of T. cruzi upon CTLA-4 blockade [47] Trypanosoma cruzi CTLA-4 induction on T cells exposed to T. cruzi-infected monocytes from indeterminate but not cardiac patients [48] reduced cytokine expression during H. polygyrus infection upon CTLA-4Ig administration [51] decreased cytokine production in ex vivo stimulated spleen cells from T. spiralis infected mice by CTLA-4Ig [52] elevated serum IgE and cytokine levels and lower parasite loads during T. spiralis infection upon CTLA-4 blockade [53] reduced worm numbers and early termination of egg production in N. brasiliensis infection by CTLA-4 blockade [54] immune suppression in chronic helminth-and filaria-infected individuals by CTLA-4 engagement [55][56][57][58] suppression of T effector functions in helminth infections by CD4 + CD25 + CTLA-4 + regulatory T cells [60][61][62][63] CTLA-4 / B7…”
Section: Btla/hvem and Light/hvem Interactions In Parasitic Infectionsmentioning
confidence: 99%